Exfoliation of Graphene by Dendritic Water-Soluble Zinc Phthalocyanine Amphiphiles in Polar Media - Methfessel, Christian; Volland, Michel; Brunner, Kristin; Wibmer, Leonie; Hahn, Uwe; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Two zinc phthalocyanines (ZnPcs) have been equipped with Newkome-type dendritic branches of increasing size and number of terminal carboxylate functional groups. The negatively charged carboxylates render these polyelectrolytes soluble in polar media such as methanol or buffered water. Sonication of the ZnPcs with graphene allowed for pronounced non-covalent binding of the ZnPc moieties on the graphene surface. These hybrid systems were fully characterized via UV/Vis, AFM, TEM, Raman and transient absorption spectroscopy, yielding insights into the electron donating nature of the novel phthalocyanine structures.
Keywords: dendrimers; donor-acceptor system; energy transfer; exfoliation; graphene

Raman Differenz-Spektroskopie für die nicht-invasive optische Biopsie des oralen Plattenepithelkarzinomes - Knipfer, Christian; Motz, Johanna; Adler, Werner; Brunner, Kristin; Gebrekidan, Medhanie; Hankel, Robert; Agaimy, Abbas; Bräuer, Andreas; Neukam, Friedrich Wilhelm; Stelzle, Florian; Will, Stefan (66. Kongress der Deutschen Gesellschaft für Mund-, Kiefer- und Gesichtschirurgie, 2016)